PEST study of CO2 capture strategy from 2007 to 2018 (2018)
Currently, CO2 capture and storage is a method approved by many countries to combat CO2 emissions, taking power and oil plants as study areas. According to many climate agreements made in the last decade, developed countries have implemented capture and storage projects in several countries, resulting in a reduction of CO2 emissions and being a key player in reducing global temperatures by 2050 using protocols, research centres and government support for future capture projects. The study conducted research on the countries with the largest number of publications on CO2 capture, considering the actions taken by different governments on issues related to politics, economics, society and technology with the help of a PEST analysis.